Disney Movie Soundtrack: Does It Give Effect to Students’ Speaking Skill? - Fika Megawati; Alda Indah Permana (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Background: The implementation of media in the learning process can be a crucial thing to support students’ competence. Meanwhile, teacher also has a role to utilize creative media in honing students’ English skill especially in speaking. This study showed that the use of song media especially Disney movies soundtrack has a significant effect for eleventh grade students’ speaking skill. However, there are several steps which should be done before applied the treatment. Methodology: This study used quasi-experimental with non-equivalent control group design. The object of this study was two classes which divided as experimental group and control group on the eleventh grade at Islamic boarding school. Furthermore, the data were collected from students’ pre-test and post-test scores. The score of test in the experimental group showed the results based on the implementation of treatment using Disney movies soundtrack, while the control group only used conventional learning. Findings: The report of finding in this study revealed that there is a significant effect toward students’ speaking skill after the researcher applied the use of English song especially Disney movies soundtrack as the media during the learning activities. Moreover, it also showed the difference between score of students in experimental group which increased than the results of students’ scores in control group. In addition, the learners still have to practice their speaking skill in daily life. Conclusion: The effect of Disney movies soundtrack becomes an effective media for eleventh grade students’ speaking skill at Islamic boarding school. Keywords: Speaking Skill, English Song, Disney Song